ASD and Genetic Associations with Receptors for Oxytocin and Vasopressin—AVPR1A, AVPR1B, and OXTR - Francis, Sunday M.; Kim, Soo-Jeong; Kistner-Griffin, Emily; Guter, Stephen; Cook, Edwin H.; Jacob, Suma (Frontiers in Neuroscience, 2016)
Background: There are limited treatments available for autism spectrum disorder (ASD). Studies have reported significant associations between the receptor genes of oxytocin (OT) and vasopressin (AVP) and ASD diagnosis, as well as, ASD-related phenotypes. Researchers have also found the manipulation of these systems affect social and repetitive behaviors, core characteristics of ASD. Consequently, research involving the oxytocin/vasopressin pathways as intervention targets has increased. Therefore, further examination into the relationship between these neuropeptides and ASD was undertaken. In this study, we examined associations between variants in the receptor genes of vasopressin (AVPR1A, AVPR1B), oxytocin (OXTR) and ASD diagnosis along with related subphenotypes. Methods: Probands were assessed using Autism Diagnostic Interview-Revised, Autism Diagnostic Observation Schedule, and clinical DSM-IV-TR criteria. Single nucleotide polymorphisms (SNPs) in AVPR1B and OXTR, and microsatellites in AVPR1A were genotyped in ~200 families with a proband with ASD. Family-based association testing (FBAT) was utilized to determine associations between variants and ASD. Haplotypes composed of OXTR SNPs (i.e. rs53576-rs2254298-rs2268493) were also analyzed due to previously published associations. Results: Using the additive inheritance model in FBAT we found associations between AVPR1B SNPs (rs28632197, p=0.005, rs35369693, p=0.025) and diagnosis. As in other studies, OXTR rs2268493 (p=0.050) was associated with diagnosis. rs2268493 was also associated with ASD subphenotypes of social withdrawal (p=0.013) and insistence on sameness (p=0.039). Further analyses demonstrated that the haplotype, rs2254298-rs2268493 was found to be significantly associated with diagnosis (A-T; p=0.026). FBAT was also used to analyze AVPR1A microsatellites (RS1 and RS3). Both length variants were found to be associated with restrictive, repetitive behaviors, but not overall diagnosis. Correction for multiple comparisons was performed for SNPs tested in each gene region, only AVPR1B SNPs remained significantly associated with ASD diagnosis. Conclusions: Autism is a heterogeneous disorder with many genes and pathways that contribute to its development. SNPs and microsatellites in the receptor genes of OT and AVP are associated with ASD diagnosis and measures of social behavior as well as restricted repetitive behaviors. We reported a novel association with ASD and AVPR1B SNPs. Understanding of genotype-phenotype relationships may be helpful in the development of pharmacological interventions for the OT/AVP system.